2015
DOI: 10.1177/0333102414566200
|View full text |Cite
|
Sign up to set email alerts
|

The place of corticosteroids in migraine attack management: A 65-year systematic review with pooled analysis and critical appraisal

Abstract: Our literature review suggests that with corticosteroid treatment, recurrent headaches become milder than pretreated headaches and later respond to nonsteroidal therapy. Single-dose intravenous dexamethasone is a reasonable option for managing resistant, severe, or prolonged migraine attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 87 publications
1
34
0
5
Order By: Relevance
“…These data indicate a hypofunction of the neuroendocrine response to stress, which could be partly responsible for the greater peripheral IL-12p70 production in this population [24], and may also represent a neuroendocrine-immune mechanism through which moderate exercise can promote a therapeutic effect on migraine. Corticosteroids still represent an effective alternative to treat resistant migraine attacks in emergency care settings [43]; these data concur with translational data showing the antinociceptive effect of corticosteroids on IL-12p70-induced hyperalgesia in rodents [30]. …”
Section: Discussionsupporting
confidence: 65%
“…These data indicate a hypofunction of the neuroendocrine response to stress, which could be partly responsible for the greater peripheral IL-12p70 production in this population [24], and may also represent a neuroendocrine-immune mechanism through which moderate exercise can promote a therapeutic effect on migraine. Corticosteroids still represent an effective alternative to treat resistant migraine attacks in emergency care settings [43]; these data concur with translational data showing the antinociceptive effect of corticosteroids on IL-12p70-induced hyperalgesia in rodents [30]. …”
Section: Discussionsupporting
confidence: 65%
“…42 Vécsei et al found that high-quality randomized trials of SM treatment in the ED are lacking. 53,54 A randomized, double-blind, placebo-controlled multicenter trial of 205 adult ED patients with migraine found no statistical benefit between 10 mg of IV dexamethasone and placebo in terms of pain freedom at the time of ED discharge. 37 Repeated doses of triptans are unlikely to provide added relief nor will they prevent recurrence of attacks.…”
Section: Expert Opinionmentioning
confidence: 99%
“…To assess viability of the cells using trypan blue, equal portions of the test hepatocytes were taken at 60, 120 and 180 minutes after incubation. 40,41 In all experiments about 80-90 percent of the viable parenchymal hepatocytes were acquired under circulation of combination of 95 % oxygen and 5 % CO 2 atmosphere. In all experiments rat parenchymal liver cells have been suspended in Krebs-Henseleit buffer media with the concentration of 10 6 cells/ml, at pH 7.4 and 37°C in round-bottom flasks 30 min prior to the addition of sumatriptan (5 mM) and/or other materials.…”
Section: Cell Preparationmentioning
confidence: 99%
“…1 It has been estimated that more than thirty million people in the United States suffer from migraine. 2 Triptans are a drugs class with proven effect in acute treatment of migraine attacks. The first member of this class of drugs sumatriptan was presented to the market within several formulations.…”
Section: Introductionmentioning
confidence: 99%